Akibat Hukum Penyebaran Berita Bohong dikaitkan dengan Undang-Undang Informasi dan Transaksi Elektronik (Studi Kasus Pernyataan Tempat Jin Buang Anak terhadap Ibu Kota Negara) (Neolectura, 2023)
In the realm of current technological advancements, the dissemination of false information has been associated with the Electronic Information and Transactions Act. A case study was conducted concerning the propagation of fake news regarding the National Capital City (IKN), purportedly being a place where jinn discard children. The research objective was to ascertain the categorization of the dissemination of such information on the YouTube platform as spreading fake news and causing harm to specific groups, as well as the corresponding criminal penalties as per the Information and Electronic Transactions Act. This study employs a normative legal approach utilizing primary and secondary data sources. Primary data was acquired through direct observation, while secondary data was obtained through a literature review and the collection of written documents pertaining to the study's title. Based on the research findings, it can be concluded that: (1) The information disseminated on YouTube regarding the State Capital (IKN) as a site for jinn to discard children constitutes the spread of false and misleading news, violating the regulations pertaining to the usage of Electronic Information, which disrupts public order, as the conveyed message has inflicted emotional harm upon specific societal groups, namely the people of Kalimantan. (2) The act of disseminating false and misleading news, as well as misusing electronic information that disrupts public order, can be subject to a maximum prison sentence of 6 years and/or a fine amounting to Rp. 1,000,000,000.00 (one billion rupiah).